Development of Learning Applications e Mole B in Badminton Games - Boby Agustan; Ramdhani Rahman (Department of Physical Education, Faculty of Health Sciences, Universitas Jenderal Soedirman, 2023)
The absence of technology based learning media in badminton activities has motivated researchers to develop new technology based learning media, so that they are easy to use and practice anywhere. The purpose of this study was to develop an electronic based badminton learning application called e Mole B. The method used in this research is research and development or R&D. Product trials were carried out at SMPN 4 Ciawigebang. With a small sample size of 10 extracurricular student respondents and a large scale test of 35 grade 7 student respondents at SMPN 4 Ciawigebang. The results of this research are based on a small scale test of 85% in the feasible category and a large scale test of 87.50% in the feasible category